IMPROVEMENT HATCHING AND QUALITY NAUPLI THROUGH THE PROVISION OF FRESH FEED DIFFERENT IN FEMALE PARENT SHRIMP VANAME ( LITOPENAEUS VANNAMEI ) A MANUSCRIPT PUBLICATION - Wahyu Parmana Saputra; Riza Rahman Hakim; Hariyadi Hariyadi (Universitas Muhammadiyah Malang, 2023)
Fresh natural feeds such as marine worms, squid, and oysters are rich sources of amino acids, proteins, and essential fatty acids, including docosahexaenoic acid (DHA), arachidonic acid (AA), and eicosapentaenoic acid (EPA), which are important for shrimp broodstock reproduction and seed production. Marine worms, in particular, contain a high protein content of approximately 56.29%. This study aims to evaluate the effects of different fresh feed types on the hatching rate (HR) of eggs and the quality of nauplii produced by female broodstock of Pacific white shrimp, Litopenaeus vannamei. The study employed an experimental method using a Completely Randomized Design (CRD). Five feeding treatments were tested with three replicates each: marine worms, squid, oysters, a combination of marine worms and oysters, and commercial pellet feed as the control. Data were analyzed using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test to determine significant differences among treatments. The results showed that different types of fresh feed significantly affected egg hatching rate. The highest hatching rate was obtained from broodstock fed marine worms, reaching 80%, which corresponded to approximately 124,630 successfully hatched larvae. Fresh feed type also had a highly significant effect on nauplius quality, as indicated by developmental stage progression at 38 hours after hatching. Broodstock fed marine worms produced nauplii that reached an average developmental stage of Nauplius VI, indicating superior larval quality compared with the other treatments. Water quality parameters during broodstock maintenance remained within acceptable ranges, with temperature ranging from 29–31°C, dissolved oxygen from 5.7 mg L⁻¹, pH at 8.0, and salinity at 31 ppt. In conclusion, the intensive use of fresh marine worms as broodstock feed can significantly improve egg hatching rate and enhance nauplius quality in Pacific white shrimp (L. vannamei).